2020
DOI: 10.18502/ijph.v48i10.3493
|View full text |Cite
|
Sign up to set email alerts
|

A Case-Control Study on the p73 G4A Gene Polymorphism and Susceptibility to Breast Cancer in an Iranian Population

Abstract: Background: The tumor protein p73 (TP73) is a homolog of TP53 family. Ectopic p73 overexpression largely mimics p53 activities as a tumor suppressor and activates the transcription of p53-responsive genes and as a result induce apoptosis. This study aimed to investigate the association between p73 G4A polymorphism and the risk of breast cancer in a northeastern Iranian population. Methods: This case-control study was performed on 105 patients who admitted in educational hospitals of Mashhad Unive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Previous research demonstrated that p73 gene polymorphisms are related to the occurrence of various cancers, including esophageal cancer [17] , rectal cancer [18] , breast cancer [19] , lung cancer [20] , and cervical cancer [21] . However, no research could be found on p73 gene polymorphism and GC susceptibility.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research demonstrated that p73 gene polymorphisms are related to the occurrence of various cancers, including esophageal cancer [17] , rectal cancer [18] , breast cancer [19] , lung cancer [20] , and cervical cancer [21] . However, no research could be found on p73 gene polymorphism and GC susceptibility.…”
Section: Introductionmentioning
confidence: 99%